A Non‐Invasive and DNA‐free Approach to Upregulate Mammalian Voltage‐Gated Calcium Channels and Neuronal Calcium Signaling via Terahertz Stimulation - Yuankun Sun; Jinli Geng; Yu Fan; Yangmei Li; Yuan Zhong; Jing Cai; Xiaodong Liu; Shaomeng Wang; Yubin Gong; Chao Chang; Yaxiong Yang; Chunhai Fan (Advanced Science)
Abstract Mammalian voltage‐gated calcium channels (CaV) play critical roles in cardiac excitability, synaptic transmission, and gene transcription. Dysfunctions in CaV are implicated in a variety of cardiac and neurodevelopmental disorders. Current pharmacological approaches to enhance CaV activity are limited by off‐target effects, drug metabolism issues, cytotoxicity, and imprecise modulation. Additionally, genetically‐encoded channel activators and optogenetic tools are restricted by gene delivery challenges and biosafety concerns. Here a novel terahertz (THz) wave‐based method to upregulate CaV1.2, a key subtype of CaV, and boost CaV1‐mediated Ca2+ signaling in neurons without introducing exogenous DNA is presented. Using molecular dynamics simulations, it is shown that 42.5 THz (7.05 µm, 1418 cm−1) waves enhance Ca2+ conductance in CaV1.2 by resonating with the stretching mode of the ‐COO− group in the selectivity filter. Electrophysiological recordings and Ca2+ imaging confirm that these waves rapidly, reversibly, and non‐thermally increase calcium influx of CaV1.2 in HEK293 cells and induce acute Ca2+ signals in neurons. Furthermore, this irradiation upregulates critical CaV1 signals, including CREB phosphorylation and c‐Fos expression, in vitro and in vivo, without raising significant biosafety risks. This DNA‐free, non‐invasive approach offers a promising approach for modulating CaV gating and Ca2+ signaling and treating diseases characterized by deficits in CaV functions.